Analysis of the Effect of Principal Leadership and Job Satisfaction on Teacher Performance (Case Study of SMK Bina Nasional Informatika Bekasi Regency) - Irvawan, Robby; Sutarya, Ade (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The purpose of this study was to analyze and evaluate the magnitude of the influence of Principal Leadership and Job Satisfaction on Teacher Performance.The research method used is a quantitative method through the distribution of questionnaires using a Likert scale as a data collection method. The population is 34 teachers and the method used in sampling is non-probability sampling. The data analysis technique used is descriptive analysis technique with simultaneous multiple regression test with regression equations to produce regression constants and coefficients for each independent variable.Based on the results of data analysis using simple and multiple linear regression analysis with the help of SPSS Version 19 for Windows, it shows that partially using the t test shows that the Principal's Leadership has a positive and significant effect of 66.6% on Teacher Performance. Partially, the results show that job satisfaction has a positive and significant effect on teacher performance by 62.5%. The variables of Principal Leadership and Job Satisfaction are jointly tested with the F test proving to have a positive and significant effect on teacher performance and the magnitude of the effect is seen of the coefficient of determination (R2) is 71.8%, while the remaining 28.2% is influenced by other variables that are not included in this research model. Thus, teacher performance will increase if the principal's leadership and teacher job satisfaction are met properly.